The capacity of personnel in disaster risk management in South African municipalities - Wentink, Gideon J.; Van Niekerk, Dewald (AOSIS, 2017)
Since 1994, fundamental transformation in South Africa in terms of disaster risk reduction taken place. The transformation process led to the promulgation of the Disaster Management Act (57/2002) (DMA) that introduced a new era of disaster risk management (DRM) in South Africa. The National Disaster Management Framework (NDMF) that followed in 2005 put clear guidelines in place for implementing the DMA and emphasised the importance of the integration and coordination of DRM activities in all spheres of government. To adhere to the requirements of the DMA regarding personnel, certain DRM structures like interdepartmental committees, disaster management centres, disaster management frameworks and disaster management advisory forums must be in place. Since the promulgation of the DMA in 2003, South African municipalities have had ample time to get the structures in place. This article tries to evaluate the degree to which South African municipalities adhere to the requirements of the DMA in terms of personnel. Municipalities were selected per province, and the research is based on a 20% representative sample of all 279 municipalities in South Africa. A mixed method of research was followed. The result of this research showed a clear lack of implementation in terms of the DMA. A number of disaster management personnel work in other municipal departments, meaning that their attention cannot fully be focused on activities relating to DRM.
Keywords: Disaster risk management; Disaster risk reduction; South African municipalities; Disaster Management Act (57/2002); National disaster management framework